“Nothing is absolute in life”: Understanding uncertainty in the context of psychiatric genetic counseling from the perspective of those with serious mental illness - Hippman, Catriona (2013)
No genetic tests are currently clinically available for serious mental illnesses such as schizophrenia and bipolar disorder. Rather, the full spectrum of genetic variants that confer susceptibility remain unknown, and estimates of probability of condition recurrence typically have the form of ranges rather than single absolute numbers. Genetic counselors have been shown to feel that the information that can be provided for patients with serious mental illness could be more confusing than helpful. However, how those with serious mental illness perceive this uncertainty remains unknown. So, to investigate this, individuals with serious mental illness participated in a psychiatric genetic counseling (GC) session and responded to a single open ended question about their reactions towards the uncertainty that they encountered in their GC session immediately and one month post-counseling (from which themes were identified), and completed the Genetic Counseling Satisfaction Scale immediately post-session (descriptive statistics applied). While some of the 37 participants were disappointed with the uncertainty, twice as many were unconcerned. Overall, responses from immediately and one month after GC were very similar; participants were very satisfied with, and found value in GC despite uncertainty, and four approaches to coping with uncertainty emerged. Ultimately, these findings offer insight into providing GC for those with serious mental illness, and potentially could be applied to other areas of GC where uncertainty lies, with downstream impact on GC practice and future research.